INTEGRASI KECAPI DALAM KURIKULUM PENDIDIKAN FORMAL BAGI MAHASISWA PENDIDIKAN SENI DRAMA TARI DAN MUSIK UNIVERSITAS NEGERI MAKASSAR - Ihsan, Andi; Saputra, Andi Taslim; Sayidiman, Sayidiman (Universitas Negeri Makassar, 2024)
This research provides an overview of the integration of the lute in formal education. The most important instrument for building culture and upholding the principles of local knowledge education and stimulating civilized behavior in society is education. In addition, there will be no separation between education and curriculum. This makes sense considering that, within the parameters of the formal education system, the curriculum is a very important teaching instrument. The curriculum must be developed so that education can meet society's expectations, because it is one of the main indicators of educational success. Because the main goal of education is to meet society's demands, a curriculum like this is relevant to society. One thing that needs to be included is the use of traditional musical instruments known as Kecapi integrated into the curriculum in formal education. Looking at the facts, the aim of the harp integration approach and formal education is to produce human resources that can function optimally in society by combining the culture of lute art and science. A program called formal education aims to combine the benefits of teaching with the delivery of high education. Universities that provide an understanding of general knowledge and produce knowledge and experience of aesthetics and other things related to objects